Review of pre-conditioning practice in mechanized deep to ultra-deep level gold mining: 26th International Symposium on Mine Planning and Equipment Selection (MPES2017). 29 – 31 August 2017, Luleå, Sweden - Sengani, F.; Zvarivadza, T. (2022)
Mining in South Africa has reached ultra- deep levels, approaching 4000m, requiring appropriate mining practices which stabilize ground conditions. As mining depth increases, the stress levels ahead of the mining faces increase with high probability of experiencing face bursting. Face- perpendicular pre- conditioning practice was employed in order to fracture the rock mass ahead of the face, so as to transfer stress further away from the face. Although the face- perpendicular pre- conditioning practice has been employed on most deep level gold mines in South Africa, rockbursts are still being experienced. The rockburst related accidents result in minor and major injuries to fatal injuries as well as machinery damage. This paper aims to highlight the effectiveness of a revised practice of four face-perpendicular pre-conditioning to five face-perpendicular pre-conditioning blasting technique in a mechanized ultra-deep level gold mine in South Africa. The investigations involved the use of underground monitoring instrumentations for the effectiveness of preconditioning practice, these include; micro seismic monitoring, Ground Penetrating Radar and borehole camera. Fragmentation of the extracted ore, fracturing on the face, side and hangingwall were taken into consideration. Vantage numerical modelling software was used to generate sigma 1 and safety factor within the section and ahead of the stope faces. It was found that most of the faces where four face-perpendicular pre- conditioning was practiced were not effectively pre- conditioned. The panels had high seismic activities and many large magnitude events compared to five face-perpendicular pre-conditioned faces. Fragmentation and face fracturing were found to have improved during the implementation of five face-perpendicular preconditioning practice. The maximum principal stress (sigma 1) and Safety Factor were found to be higher during four face- perpendicular preconditioning practice, while these were found to be reduced during the five face-perpendicular preconditioning practice.